My Fall: Historic Testimony from the former President of Bolivia Carlos Mesa Gisbert about his “Surrounded Presidency” (2003/2005) - Mendoza Pinto, Juan Eduardo; Téllez Lúgaro, Eduardo (Revista Tribuna Internacional, 2016)
We present an unpublished document on the poignant events experienced by the State and the Bolivian society in the difficult situation 2003/2005, associated with the presidency of Carlos Mesa G., leaving us here a direct witness, the highest level on this trance historical, of great value to the contemporary history of Latin America.